KAJIAN ETNOMUSIKOLOGI NYANYIAN DESA YO DAY NENGO SEBAGAI PENGIRING TARIAN LEGO-LEGO PADA MASYARAKAT DESA KAMAIFUI, KECAMATAN MATARU, SUKU ABUI, KABUPATEN ALOR - Relin Yosi Huka; Imanuel Letma; Novi Marliyani Nafi (Institut Agama Kristen Negeri Kupang, 2022)
This study aims to describe and analyze the singing accompaniment to the Lego-lego dance entitled Yo Day Nengo Village, in the people of Kamaifui village, Mataru sub-district, Alor district, the authors obtained the results, namely. The method used is a qualitative method with an ethnographic approach, especially ethnomusic. The results showed (a) Lego-lego is a traditional dance belonging to the Kamaifui people; (b) the traditions that are still maintained by the people of Kamaiifui village to this day are the cakalele dance, war dance, gong and moko as traditional musical instruments and women's belis tools, and the Lego-lego dance. (c) The function of Yo Day Nengo Village singing is as a means of communication, a function of aesthetic appreciation, a function related to social norms, a function of entertainment, a function as a symbolic representation. (c) Yo Day Nengo Village Song is an accompaniment song that is general in nature and easy to be sung by all levels of society. (d) The text of the Yo Day Nengo Village song contains syllabic and melismatic. (e) The scale of the singing of Yo Day Nengo Village consists of five notes.